Non-genetic factors affecting calving interval and weaning weight in a buffalo herd located in well drained savannas, Guárico state, Venezuela - N. Martínez; B. Birbe; P. Herrera; R. Bello; O. Colmenares (Italian Journal of Animal Science, 2010)
The main focus of this research was to evaluate non-genetic factors affecting calving interval (CI) and weaning weight (WW) on a buffalo herd located in well drained savannas of Guárico state, Venezuela. The study involved records (1997-2001) related to monthly frequency of calving (n=486); calving interval (n=365) and weaning weight (n=376). Data analysis included year and calving season, calf sex, cow age and the interactions for CI. For WW, age at weaning was also included in the statistical analysis. Results revealed significant differences for calving distribution per year (P≤0.05) associated with year-on-year climatic factor changes and progressive herd stabilization. CI averaged 378 ± 1.8 (X – ± S.E.) days, with a coefficient of variation (CV) of 7.3% and a significant effect of calving month (P ≤ 0.05). CI frequency distribution for herd showed 75% cows lower than 400 days. Female age at calving was not significant (linear or quadratic) due it was a young herd, with less than 2.6% animals older than 11 years. WW averaged 130.4±1.9 kg and CV of 24.4%; age to weaning 238.7±3.2 days, with calving month and age to weaning showing significant effect, while the weight average daily gain was 128g per animal. These findings suggest buffalo’s productive and reproductive potential under tropical conditions.